Influence of climatic factors on tree growth in riparian forests in the humid and dry savannas of the Volta basin, Ghana - Boakye, Emmanuel Amoah; Gebrekirstos, Aster; N’da Hyppolite, Dibi; Barnes, Victor Rex; Kouamé, François N.; Kone, Daouda; Porembski, Stefan; Bräuning, Achim (Trees-Structure and Function, 2016)
Riparian trees in savannas have a potential for dendro-climatic studies, but have been neglected hitherto. We examined ring-width series of Afzelia africana (evergreen) and Anogeissus leiocarpus (deciduous) to study the influence of climatic factors on the growth of riparian trees in the humid (HS) and dry (DS) savanna zones of the Volta basin in Ghana. A total of 31 stem discs belonging to A. africana and A. leiocarpus were selected from HS and DS to establish species-specific local chronologies of tree growth. Each individual of A. africana and A. leiocarpus from the two savanna sites showed distinct growth rings. Cross-dating of individual tree-ring patterns was successful using standard dendrochronological techniques. The mean annual growth rates of A. africana in the HS (1.38 ± 0.09) and DS (1.34 ± 0.08) were not statistically different. Furthermore, mean annual growth rate of A. leiocarpus in the DS (3.75 ± 0.27) was higher than in the HS (2.83 ± 0.16) suggesting that species in drier environment can have higher growth rates when sufficient soil moisture is available. The growth rates of both species at the same sites were different, which might indicate different water use strategies. High correlations of individual tree-ring series of A. africana and A. leiocarpus trees at HS and DS suggest a strong climatic forcing controlled by the seasonal movement of the inter-tropical convergence zone. The annual growth of A. africana and A. leiocarpus at both the HS and DS was significantly correlated with local temperature and precipitation. The negative correlations of the growth of the two tree species to global sea surface temperatures were however, indications that the growth of riparian forests can be impacted during El Niño-Southern Oscillation years. The result of our study shows that riparian trees in the humid and dry savanna zones of West Africa can be successfully used for dendrochronological studies.
Keywords: Riparian forests; Humid savanna; Dry savanna; Dendrochronology; Tree growth; West Africa